REVIEW ARTIKEL STRUKTUR SEL EPIDERMIS DAN STOMATA ALLIUM CEPA DAN AGLAI ODORATA - Nasanda, Fika; Mustakim, Ardi (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
This study aims to analyze the structure of the epidermal cells and stomata in two plant species, namely Allium cepa (onion) and Aglaia odorata (champaca). The methods used in this research include sample preparation, staining, and microscopic observation. The results show that the epidermal cell structure of both species has significant morphological differences. The epidermis of Allium cepa exhibits larger, densely arranged cells with fewer stomata compared to Aglaia odorata, which has smaller epidermal cells and more stomata. These differences can be attributed to the adaptation of both species to their growing environments. This finding provides a better understanding of the morphological adaptations of plants in facing different environmental conditions.